An Observational Study to Compare the Anti Anginal Efficacy of Ranolazine versus Nicorandil in Ischemic Heart Disease Patients Attending a Tertiary care Hospital in Kolkata - Mallick, Arup R.; Saha, Pradip; Sengupta, Ishita; Sengupta, Gairik; Bhattacharya, Paramartha; Dutta, Soumya K. (Universitas Padjadjaran, Indonesia, 2024)
Ischemic Heart disease (IHD) occurs due to an imbalance between myocardial oxygen supply and demand. In stable IHD, second-line anti-anginal drugs like Ranolazine and Nicorandil are used as add-on therapy with first-line agents like Nitrates and beta-blockers. Our study compared the efficacy of Ranolazine versus Nicorandil utilizing the patient’s responses to the Short Seattle Angina Questionnaire (SAQ7) score. A prospective observational study on stable IHD patients attending the cardiology Outpatient Department (OPD) of IPGME&R and SSKM Hospital, Kolkata, with either Ranolazine or Nicorandil as add-on therapy (50 patients in each group). SAQ7 score was recorded at baseline and three follow-up visits (1.5, 3, and 6 months). Adverse effects and the changes in HbA1C levels in diabetic patients among these patients were also compared. There was a significant increase in SAQ7 score in Ranolazine [median (IQR) - 26.50 (25.00 - 29.25) to 32.00 (30.75 - 34.00), p < 0.0001] and also in Nicorandil [median (IQR) - 27.00 (24.00 - 30.00) to 32.50 (31.00 - 34.00), p < 0.0001] group in third follow up visits from baseline. The comparison between the groups didn’t show any significant changes. There were no significant changes in HbA1C levels between the pre and post-treatment period. Adverse effects were more in the Nicorandil group. Both drugs significantly improved IHD patients’ symptom control and were well tolerated. There were no significant differences in the change of HbA1C level in Diabetic patients. However, a larger study is required to decide whether these drugs can be used as a single agent alone.